Impact of Decoding Work within a Professional Program. (June 2017) - Yeo, Michelle; Lafave, Mark; Westbrook, Khatija; McAllister, Jenelle; Valdez, Dennis; Eubank, Breda
Abstract : This chapter demonstrates how Decoding work can be used productively within a curriculum change process to help make design decisions based on a more nuanced understanding of student learning and the relationship of a professional program to the field.